Macrophage polarization and activation in response to implant debris: influence by "particle disease" and "ion disease" - Konttinen, Yrjo T; Pajarinen, Jukka; Takakubo, Yuya; Gallo, Jiri; Nich, Christophe; Takagi, Michiaki; Goodman, Stuart B (Journal of long-term effects of medical implants, 2014)
Macrophages derive from human embryonic and fetal stem cells and from human bone marrow-derived blood monocytes. They play a major homeostatic role in tissue remodeling and maintenance facilitated by apoptotic "eat me" opsonins like CRP, serum amyloid P, C1q, C3b, IgM, ficolin, and surfactant proteins. Three subsets of monocytes, classic, intermediate, and nonclassic, are mobilized and transmigrate to tissues. Implant-derived wear particles opsonized by danger signals regulate macrophage priming, polarization (M1, M2, M17, and Mreg), and activation. CD14(+) monocytes in healthy controls and CD16(+) monocytes in inflammation differentiate/polarize to foreign body giant cells/osteoclasts or inflammatory dendritic cells (infDC). These danger signal opsonins can be pathogen- or microbe-associated molecular patterns (PAMPs/MAMPs), but in aseptic loosening, usually are damage-associated molecular patterns (DAMPs). Danger signal-opsonized particles elicit "particle disease" and aseptic loosening. They provide soluble and cell membrane-bound co-stimulatory signals that can lead to cell-mediated immune reactions to metal ions. Metal-on-metal implant failure has disclosed that quite like Ni(2+), its neighbor in the periodic table Co(2+) can directly activate toll-like receptor 4 (TLR4) as a lipopolysaccharide-mimic. "Ion disease" concept needs to be incorporated into the "particle disease" concept, due to the toxic, immune, and inflammatory potential of metal ions.
Keywords: Arthroplasty, Replacement; Cell Differentiation; polarita buněk; Prosthesis Failure; Cell Polarity; Joint Prosthesis; selhání protézy; Macrophages; makrofágy; Macrophage Activation; aktivace makrofágů; buněčná diferenciace; Humans; protézy kloubů; artroplastiky kloubů; lidé